2000
DOI: 10.1182/blood.v96.8.2902.h8002902_2902_2904
|View full text |Cite
|
Sign up to set email alerts
|

CFU-S11 activity does not localize solely with the aorta in the aorta-gonad-mesonephros region

Abstract: The aorta-gonad-mesonephros (AGM) region is a potent hematopoietic site in the midgestation mouse conceptus and first contains colony-forming units-spleen day 11 (CFU-S 11 ) at embryonic day 10 (E10). Because CFU-S 11 activity is present in the AGM region before the onset of hematopoietic stem cell (HSC) activity, CFU-S 11 activity in the complex developing vascular and urogenital regions of the AGM was localized. From E10 onward, CFU-S 11 activity is associated with the aortic vasculature, and is found also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…CFUs precursors were present in both AGM and YS by E9 since cultures of either tissue at this stage generated CFU-S (42). In vivo engraftment was obtained with cells from the E10.5 dorsal aorta and vitelline/umbilical artery (80,81). Quantitation of long-term repopulating stem cell numbers by limiting dilution assay has shown that they first appear in the AGM at E10.5 and are present in equal numbers in AGM, YS, circulation, and early liver rudiment by E11 (43).…”
Section: Development Of Hematopoiesis In the Aorta-gonad Mesonephros mentioning
confidence: 99%
“…CFUs precursors were present in both AGM and YS by E9 since cultures of either tissue at this stage generated CFU-S (42). In vivo engraftment was obtained with cells from the E10.5 dorsal aorta and vitelline/umbilical artery (80,81). Quantitation of long-term repopulating stem cell numbers by limiting dilution assay has shown that they first appear in the AGM at E10.5 and are present in equal numbers in AGM, YS, circulation, and early liver rudiment by E11 (43).…”
Section: Development Of Hematopoiesis In the Aorta-gonad Mesonephros mentioning
confidence: 99%
“…1C). The AGM region was subdissected using 27G needles into the aorta, with surrounding mesenchymal tissue (AM), and the urogenital ridges, containing the pro/mesonephros and the gonads (UG) (de Bruijn et al, 2000a;de Bruijn et al, 2000b). Subdissected tissues from litters with at least seven embryos were pooled and either explant cultured at the air-medium interface on 0.1% gelatin-coated 6-well plates (Costar, Badhoevedorp, NL) or cultured as a single cell suspension (after a 15 minute incubation with 0.25% trypsin and vigorous pipetting) on 0.1% gelatin-coated 6-well plates in stromal medium: 50% long-term culture medium (M5300, StemCell Technologies, Vancouver, BC, Canada), 15% FCS, 35% AlphaMEM, supplemented with antibiotics (penicillin and streptomycin; Gibco), Glutamax-I (Gibco) and 10 µM β-mercaptothanol (Merck Eurolab, Darmstadt, Germany).…”
Section: Transgene and Expression Analysismentioning
confidence: 99%
“…The generation of the first transplantable hematopoietic stem cells (HSCs) initiates in the dorsal aorta of the aortagonad-mesonephros (AGM) region at embryonic day 10.5 (E10.5) in mouse embryos (de Bruijn et al, 2000;Medvinsky and Dzierzak, 1996). It involves activating a hematopoietic transcriptional program in a subset of endothelial cells (ECs), as a result of a number of internal and external signals, which drives these cells to adopting a hematopoietic fate (Ottersbach, 2019).…”
Section: Introductionmentioning
confidence: 99%